Effect of different organics and Sulphur sources on growth and yield of Sesame (Sesamum indicum L.): Effect of different organics and Sulphur sources on growth and yield of Sesame (Sesamum indicum L.) - S D BHANDEKAR; A K GHOTMUKALE; K YASWANTH ACHARI (Journal of Oilseeds Research, 2023)
A field experiment was carried out during rainy season-2021 at Experimental farm, Oilseeds Research Station, Latur, to evaluate “Effect of different organics and Sulphur sources on growth and yield of Sesame (Sesamum indicum L.)” variety TLT-10. Application of Vermicompost @ 2.5 t/ha (T2) and Gypsum @ 500kg/ha (S3 ) produced higher growth, yield and quality traits along with good net returns and B:C ratio.